Faktor-faktor yang Mempengaruhi Adopsi Produk Ramah Lingkungan di Kalangan Milenial Perkotaan - Uning Heri Gagarin; Yeni Trisna Purba; Frans Favo Purba S (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to analyze the factors influencing the adoption of eco-friendly products among urban millennials in Indonesia and to develop a predictive model and effective intervention strategies to reduce the green attitude–behavior gap. The research employed a mixed-methods design using a sequential explanatory approach: a quantitative phase through surveys to test relationships among variables and hypotheses, followed by a qualitative phase using in-depth interviews, focus group discussions, expert interviews, and observations in retail outlets. The population consisted of urban millennials aged 25–40 living in metropolitan cities with at least one million residents. The quantitative sample included 600 respondents, while the qualitative phase involved 40 participants plus experts and retail observations. The findings indicate that eco-friendly product adoption is significantly shaped by internal factors (environmental values and knowledge), external factors (social influence and economic conditions), and product characteristics (quality and innovativeness). Environmental values positively affect environmental concern (β = 0.52; p < 0.001), while price sensitivity negatively affects purchase intention (β = −0.32; p < 0.001). Product availability also enhances perceived behavioral control (β = 0.40; p < 0.001). The study further confirms moderating effects of green self-identity, income level, urban infrastructure, and product innovativeness. Four main adoption segments were identified (Green Champions, Selective Adopters, Price-sensitive Considerers, and Skeptical Non-adopters). The study proposes the Urban Millennial Green Adoption Model (UMGAM), integrating input factors (individual, social, contextual), processing mechanisms (cognitive, affective, behavioral), and adoption and impact outcomes. The results are expected to guide producers, retailers, and policymakers in designing more targeted strategies to promote sustainable consumption.